Bimetal sulfide-based photocatalyst, preparation method and application thereof in hydrogen production coupling plastic degradation
By constructing the FeCo-LDH/Cd1-xZnxS composite photocatalyst, the problem of slow oxidation kinetics of the photocatalyst in water and difficulty in using oxidizing groups in plastics is solved, and efficient photocatalytic hydrogen production is achieved and the performance and application value of the catalyst is significantly improved.
Patent Information
- Application Number
- CN202411988015.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing photocatalysts have slow oxidation kinetics in water, which limits the efficiency of photocatalytic hydrogen production, and it is difficult to effectively utilize oxidative groups in waste plastics for coupled oxidation and degradation.
By using bimetal sulfide-based photocatalyst, the energy band structure of the material is regulated, the spectral response range is broadened, and the coupling between photocatalytic water decomposition and plastic degradation is achieved.
The photocatalytic hydrogen production rate and plastic degradation efficiency were significantly improved. The photocatalytic hydrogen production rate of 5% LDH/Cd0.5Zn0.5S reached 3.67mmol·g-1·h-1, which was 2.28 times that of pure Cd0.5Zn0.5S, and the complete conversion of ethylene glycol was achieved, with a single degradation product, which was conducive to the collection and purification of later products.
Smart Images

Figure CN119771447A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a hydrogen production catalyst, and in particular to a bimetallic sulfide-based photocatalyst, a preparation method and application thereof in hydrogen production coupled with plastic degradation. Background Art
[0002] Plastic pollution has become a global challenge. The total amount of plastic waste in the world exceeds 52.1 million tons per year, of which only 9% is recycled, 19% is incinerated, about 50% is landfilled, and the remaining 22% is abandoned in unmanaged landfills, burned in the open air or leaked into the environment. Chemical recycling is an important technical route for the recycling of waste plastics, and is of great significance for building a plastic pollution control system and energy resource security. Solar photocatalytic water decomposition to produce hydrogen is considered to be one of the important ways to solve energy crises and environmental problems. However, the slow kinetics of water oxidation has become one of the important factors restricting the efficiency of photocatalytic hydrogen production. Finding an oxidation half-reaction coupled with water reduction to produce hydrogen is more in line with the concept of sustainable development. Plastics contain rich groups, are oxidizing, and have the conditions to participate in the oxidation half-reaction. If waste plastics can be upgraded and recycled to produce hydrogen, it can not only solve the problem of environmental pollution, but also "turn waste into treasure" to achieve resource utilization.
[0003] Designing high-performance photocatalysts is the key to coupling photocatalytic water splitting to hydrogen production with oxidative degradation of waste plastics. 1-x Zn x S is a very ideal new semiconductor photocatalyst, which has the advantages of zinc sulfide (ZnS) and cadmium sulfide (CdS), and has a variety of crystal structures, adjustable band gap, excellent visible light response ability and chemical stability. It is widely used in the field of photocatalysis. 1-x Zn x The rapid recombination of photogenerated electrons and holes in the S solid solution limits its photocatalytic efficiency. Summary of the invention
[0004] The object of the present invention is to provide a bimetallic sulfide-based photocatalyst having excellent performance of photocatalytic water decomposition to produce hydrogen coupled with plastic degradation.
[0005] The technical solution adopted by the present invention to solve its technical problem is:
[0006] A method for preparing a bimetallic sulfide-based photocatalyst, the method comprising the following steps:
[0007] S1, Cd 1-x Zn x Preparation of S nanosheets:
[0008] Take L-cysteine and zinc nitrate, stir them thoroughly in a diethylenetriamine (DETA) aqueous solution at room temperature, pour the mixed solution into a polytetrafluoroethylene reactor for sealing, and react at a constant temperature of 150°C ± 10°C in a forced air drying oven for 4h-6h;
[0009] After the reaction, the synthesized product was washed by centrifugation with water and ethanol for multiple times, dried and collected at 60°C ± 5°C, and the obtained powder was dissolved in DETA aqueous solution, and cadmium chloride was added under continuous stirring to make it dispersed evenly. Then the mixed solution was poured into a polytetrafluoroethylene reactor for packaging, and reacted at a constant temperature of 180°C ± 10°C in a blast drying oven for 5h-7h. After the reaction, the synthesized product was collected, washed multiple times, and dried to obtain Cd 1-x Zn x S nanosheets, the ratio of raw materials is controlled so that 0.5≤x≤0.75;
[0010] S2. Preparation of FeCo-LDH:
[0011] Dissolve (NH4)2Fe(SO4)2·6H2O, Co(NO3)2·6H2O, Co(NH2)2 and NH4F in an appropriate amount of water, and stir continuously for more than 30 minutes to mix them evenly; transfer the mixed solution to a polytetrafluoroethylene-lined autoclave and react at a constant temperature of 120℃±5℃ for 7h-8h, cool to room temperature after the reaction, and collect the sample by centrifugation washing at least three times with deionized water and anhydrous ethanol, and finally dry it in a vacuum oven at 80℃±5℃ overnight to obtain the sample FeCo-LDH;
[0012] S3, FeCo-LDH / Cd 1-x Zn x Preparation of S composite photocatalytic materials:
[0013] FeCo-LDH and Cd 1-x Zn x S is mixed in a mass ratio of 1-7:100, ultrasonically dispersed in an appropriate amount of anhydrous ethanol for 2-3 hours, and then evaporated to dryness in a water bath to obtain a bimetallic sulfide-based photocatalyst.
[0014] Constructing heterostructures, surface sensitization or doping are all common strategies to improve their photocatalytic performance. Among them, constructing heterojunctions is an ideal method to enhance interfacial charge separation. Layered Double Hydroxide (LDH), as a new type of semiconductor material, has a large specific surface area, excellent electrical conductivity, abundant active sites and good stability. It has shown excellent performance in various photocatalytic applications such as photocatalytic degradation of organic pollutants, photolysis of water to produce hydrogen, and photocatalytic CO2 reduction. Therefore, the present invention uses layered hydrotalcite FeCo-LDH to modify Cd 1-x Znx S, construct FeCo-LDH / Cd 1-x Zn x S composite photocatalyst is used to regulate the energy band structure of the material to broaden the spectral response range and achieve the improvement of photocatalytic water decomposition and hydrogen production coupled with plastic degradation performance.
[0015] The present invention uses FeCo-LDH as a co-catalyst and constructs FeCo-LDH / Cd 1-x Zn x S composite catalyst was used to study the photocatalytic hydrogen production coupled with PET plastic degradation performance. The results showed that 5% LDH / Cd 0.5 Zn 0.5 S exhibited an excellent hydrogen evolution rate of 3.67 mmol·g -1 ·h -1 , which is due to 5% LDH / Cd 0.5 Zn 0.5 S has excellent synergistic effects in charge separation and light absorption. The photocatalytic oxidation products of plastics were analyzed by H NMR spectra. PET treated with alkaline solution was completely converted into acetate and a small amount of methanol. According to the results of UV, transient fluorescence spectroscopy and electrochemistry, it was proved that the introduction of an appropriate amount of FeCo-LDH significantly promoted the separation of electrons and holes, thereby improving the photocatalytic activity. 0.5 Zn 0.5 The mechanism of S photocatalytic hydrogen production coupled with plastic degradation is speculated, and Cd 0.5 Zn 0.5 The holes in the valence band of the S catalyst surface oxidize PET to small organic molecules, and the electrons in the conduction band of FeCo-LDH reduce H2O to H2.
[0016] As a preference, FeCo-LDH and Cd 1-x Zn x The mass ratio of S is 5-7:100. FeCo-LDH and Cd 1-x Zn x The optimal mass ratio of S is 5:100.
[0017] Preferably, S1, in the DETA aqueous solution mixed with L-cysteine and zinc nitrate, the volume ratio of DETA to H2O is 4:1; in the DETA aqueous solution in which the obtained powder is dissolved, the volume ratio of DETA to H2O is 2:1.
[0018] As a preference, in Cd 1-x Zn xIn the preparation of S, when x=0.5, the usage ratio of L-cysteine, zinc nitrate and cadmium chloride is 6mmol:6mmol:0.6mmol respectively; when x=0.75, the usage ratio of L-cysteine, zinc nitrate and cadmium chloride is 6mmol:6mmol:0.3mmol respectively.
[0019] Preferably, in S2, the usage ratio of (NH4)2Fe(SO4)2·6H2O, Co(NO3)2·6H2O, Co(NH2)2 and NH4F is 1.2 mol:2.4 mol:4.8 mol:4.8 mol.
[0020] Preferably, Cd 1-x Zn x The x in S is 0.5, FeCo-LDH and Cd 1-x Zn x The mass ratio of S is 5:100.
[0021] A bimetallic sulfide-based photocatalyst prepared by the preparation method of the present invention.
[0022] An application of the bimetallic sulfide-based photocatalyst described in the present invention in hydrogen production coupled with plastic degradation.
[0023] Preferably, in a sealed environment, 30-50 mg of the catalyst is dispersed in 70 ml of a 0.025 wt%-0.035 wt% polyethylene terephthalate (PET) alkaline solution for reaction, and the reaction temperature is maintained at 5°C.
[0024] The beneficial effects of the present invention are:
[0025] 1. Cd with different Cd / Zn ratios 1-x Zn x S hydrogen production performance comparison, among which Cd 0.5 Zn 0.5 S has the best hydrogen production performance, which is 1.61mmol·g -1 ·h -1 ;
[0026] 2. FeCo-LDH / Cd prepared by the present invention 0.5 Zn 0.5 S nanocomposite catalyst, FeCo-LDH and Cd 0.5 Zn 0.5 S are in close contact with each other to form a heterojunction, and Zn, Cd, S, Fe, Co and O elements are evenly distributed in the heterostructure; 0.5 Zn 0.5 Compared with FeCo-LDH, 5% LDH / Cd 0.5 Zn 0.5The corresponding peak positions of S shifted to different degrees, indicating that Cd 0.5 Zn 0.5 There is a strong electronic interaction at the interface between S and FeCo-LDH;
[0027] 3. FeCo-LDH, Cd 0.5 Zn 0.5 S and 5% LDH / Cd 0.5 Zn 0.5 The carrier lifetimes of S are 1.14ns, 1.06ns and 1.45ns respectively. The composite sample 5% LDH / Cd 0.5 Zn 0.5 The carrier lifetime of S is longer than that of pure Cd 0.5 Zn 0.5 S and FeCo-LDH are long, indicating that the sample 5% LDH / Cd 0.5 Zn 0.5 S has high efficiency in photogenerated carrier transfer. 5% LDH / Cd 0.5 Zn 0.5 The S composite showed the highest photocurrent, further confirming that the 5% LDH / Cd 0.5 Zn 0.5 S has the strongest photogenerated carrier separation and transfer efficiency, which improves the photocatalytic activity.
[0028] 4. In the hydrogen production coupled plastic degradation performance test, when pure Cd 0.5 Zn 0.5 After S is combined with LDH, the sample is 5% LDH / Cd 0.5 Zn 0.5 The photocatalytic hydrogen production rate of S reached 3.67 mmol·g -1 ·h -1 , for pure Cd 0.5 Zn 0.5 S is 2.28 times. When LDH / Cd is further increased 0.5 Zn 0.5 The loading amount of LDH in S will reduce the photocatalytic hydrogen production activity. After the photocatalytic reaction, ethylene glycol is almost completely converted into acetate. This result confirms that the catalyst of the present invention achieves the purpose of plastic degradation while producing hydrogen. Compared with similar catalysts, the catalyst of the present invention can completely convert ethylene glycol, further proving the high catalytic activity; the degradation product is single, which is conducive to the collection and purification of the later products, increasing the practical application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 FeCo-LDH / Cd 1-x Zn x Schematic diagram of the synthesis process of S;
[0030] Figure 2 Yes(a)Cd 1-x Zn x XRD spectrum of S solid solution; (b) Cd 1-x Zn x Photocatalytic hydrogen production rate of S solid solution;
[0031] Figure 3 (a) XRD pattern of the sample; (bc) Cd 0.5 Zn 0.5 TEM image of S; (de) TEM image of FeCo-LDH; (fg) 5% LDH / Cd 0.5 Zn 0.5 TEM image of S; (h) 5% LDH / Cd 0.5 Zn 0.5 Element distribution diagram of S;
[0032] Figure 4 It is CD 0.5 Zn 0.5 S, FeCo-LDH and 5% LDH / Cd 0.5 Zn 0.5 XPS spectra of S: (a) Cd 3d fine spectrum; (b) Zn 2p fine spectrum; (c) S2p fine spectrum; (d) Fe 2p fine spectrum; (e) Co 2p fine spectrum; (f) O1s fine spectrum;
[0033] Figure 5 (a) UV-vis DRS of the sample; (b) Cd 0.5 Zn 0.5 Band gap diagram of S and LDH; (c) transient fluorescence spectrum; (d) transient photocurrent response;
[0034] Figure 6 (a) Photocatalytic hydrogen production activity of different synthesized samples; (b) 5% LDH / Cd 0.5 Zn 0.5 The nuclear magnetic resonance hydrogen spectrum of the PET plastic reaction solution before and after 4 hours of photocatalytic reaction ( 1 H-NMR). DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described in detail below through specific embodiments. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any form of modification and / or change made to the present invention will fall within the protection scope of the present invention.
[0036] In the present invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0037] Unless otherwise specified, the reagents used in the following examples can be purchased from conventional biochemical reagent stores.
[0038] All reagents used in the following examples were analytical grade reagents purchased from Aladdin and used without further purification.
[0039] Example: Preparation of photocatalyst
[0040] a) Cd 1-x Zn x Preparation of S nanosheets. Weigh 6mmol L-cysteine and 6mmol zinc nitrate, dissolve in a beaker containing 60ml diethylenetriamine (DETA) and deionized water (volume ratio of DETA:H2O = 4:1), and stir at room temperature for 30min. Pour the mixed solution into a polytetrafluoroethylene reactor and seal it. React at a constant temperature of 150℃ in a forced air drying oven for 5h. After the reaction, the synthesized product was washed with deionized water and ethanol by centrifugation several times, and dried at 60℃. Subsequently, the prepared powder was dissolved in a mixed solvent of DETA and distilled water (volume ratio of DETA:H2O = 2:1), and cadmium chloride was added under continuous stirring (when x = 0.25, 0.5 and 0.75, the amount of cadmium chloride added was 0.9 mmol, 0.6 mmol and 0.3 mmol, respectively) to make it dispersed evenly. Then the mixed solution was poured into a polytetrafluoroethylene reactor for packaging, and the reaction was carried out at a constant temperature of 180°C in a blast drying oven for 6 hours. After the reaction, the synthetic product was collected, washed several times and dried to obtain Cd 1-x Zn x S nanosheets (0≤x≤1).
[0041] b) Preparation of FeCo-LDH. Dissolve 1.2mmol(NH4)2Fe(SO4)2·6H2O, 2.4mmol Co(NO3)2·6H2O, 4.8mmol Co(NH2)2 and 4.8mmol NH4F in 40mL deionized water in turn and stir for 30 minutes to mix evenly. Transfer the mixed solution to a polytetrafluoroethylene-lined autoclave and react at 120°C for 8h. After the reaction, cool to room temperature, wash the sample three times with deionized water and anhydrous ethanol, and finally dry it in a vacuum oven at 80°C overnight to obtain the sample FeCo-LDH, named LDH.
[0042] c)FeCo-LDH / Cd 1-x Zn xPreparation of composite photocatalytic materials. Different masses of FeCo-LDH (1 mg, 3 mg, 5 mg and 7 mg) and 100 mg Cd 1-x Zn x S was added to a small beaker containing 20 mL of anhydrous ethanol and ultrasonically dispersed for 3 h, and then evaporated to dryness in a water bath. After evaporation, the product was labeled as X% LDH / Cd 1-x Zn x S (X = 1, 3, 5 and 7) samples. Sample FeCo-LDH / Cd 1- x Zn x The synthesis process of S is as follows Figure 1 shown.
[0043] Characterization of photocatalysts
[0044] The crystal structure of the samples was determined by X-ray powder diffractometer (XRD). The morphology and microstructure of the samples were characterized by transmission electron microscopy (TEM). The ultraviolet-visible diffuse reflectance spectroscopy (UV-vis DRS) was used to study the FeCo-LDH / Cd 1-x Zn x The light absorption characteristics of S composite photocatalyst; the fluorescence lifetime of the sample was obtained by steady-state fluorescence spectroscopy (PL) and transient fluorescence spectroscopy (TRPL). The photoelectrochemical test experiment was carried out on an electrochemical workstation equipped with three electrodes.
[0045] 1. Cd 1-x Zn x Crystal structure and property optimization of S solid solution
[0046] Cd with different Cd / Zn ratios 1-x Zn x The XRD spectra of S (x = 0.25, 0.5 and 0.75) are as follows Figure 2 (a) shows that both ZnS and CdS have hexagonal wurtzite structures, corresponding to standard PDF cards 05-0566 and 41-1049, respectively. 2+ When doped into the ZnS lattice, the diffraction peak of ZnS gradually shifts to a lower angle. This is because Cd 2+ Radius Greater than Zn 2+ Radius Cd 2+ The Cd2+ enters the ZnS lattice and increases the lattice spacing of ZnS. The continuous shift of the diffraction peak indicates that Cd2+ 1-x Zn x S solid solutions (x = 0.25, 0.5 and 0.75) were successfully prepared. Figure 2 (b) Cd with different Cd / Zn ratios 1-x Znx S hydrogen production performance comparison, among which Cd 0.5 Zn 0.5 S has the best hydrogen production performance, which is 1.61mmol·g -1 ·h -1 .
[0047] Therefore, we selected the solid solution Cd with the best hydrogen production performance. 0.5 Zn 0.5 S was used as the subsequent research object to study the loading of different amounts of FeCo-LDH on Cd 0.5 Zn 0.5 The role of S in photocatalytic hydrogen production coupled to plastic degradation.
[0048] 2. LDH / Cd 0.5 Zn 0.5 Structure and morphology of S composite photocatalyst
[0049] Figure 3 (a) is Cd 0.5 Zn 0.5 S, FeCo-LDH and different LDH / Cd 0.5 Zn 0.5 XRD patterns of the composite materials, in which FeCo-LDH and Cd 1-x Zn x The mass ratio of S was 0, 1:100 (1%), 3:100 (3%), 5:100 (5%), and 7:100 (7%). The characteristic diffraction peaks of FeCo-LDH at 11.8° and 23.6° correspond to the (003) and (006) crystal planes of FeCo-LDH (PDF#50-0235). 0.5 Zn 0.5 Cd was observed in the XRD patterns of S samples. 0.5 Zn 0.5 The addition of LDH did not change the crystal form of Cd0.5Zn0.5S, and with the increase of LDH loading, the LDH / Cd 0.5 Zn 0.5 The (003) and (006) diffraction peaks of FeCo-LDH gradually appeared in S, confirming that LDH / Cd 0.5 Zn 0.5 The successful preparation of S. Figure 3 (b) shows pure Cd 0.5 Zn 0.5 S is an irregular porous nanosheet structure, HRTEM image (such as Figure 3 (c) The lattice fringes with a spacing of 0.32 nm belong to hexagonal Cd 0.5 Zn 0.5 (111) crystal plane of S. Figure 3 The transmission electron microscopy image in (d) shows that FeCo-LDH is a one-dimensional rod-like structure. The HRTEM image ( Figure 3 The lattice fringes with a spacing of 0.44 nm in (e) correspond to the crystal planes of FeCo-LDH. Figure 3 (f) 5% LDH / Cd 0.5 Zn 0.5 TEM images of S nanocomposites, Cd 0.5 Zn 0.5 The surface of S nanosheets is partially covered by FeCo-LDH nanostructures. Figure 3 (g) shows that 5% LDH / Cd 0.5 Zn 0.5 The HRTEM image of S shows that the lattice fringes of 0.44 nm and 0.32 nm are attributed to FeCo-LDH and Cd, respectively. 0.5 Zn 0.5 These results not only prove that FeCo-LDH / Cd 0.5 Zn 0.5 S nanocomposites were successfully synthesized and the FeCo-LDH and Cd 0.5 Zn 0.5 The close contact between S forms a heterojunction. Figure 3 The elemental mapping image in (h) shows that Zn, Cd, S, Fe, Co, and O are uniformly distributed in the heterostructure, further reflecting the FeCo-LDH and Cd 0.5 Zn 0.5 S is closely connected.
[0050] XPS analysis of Cd 0.5 Zn 0.5 S, FeCo-LDH and 5% LDH / Cd 0.5 Zn 0.5 Changes in the surface valence state of S catalyst. Figure 4 (a) is Cd 0.5 Zn 0.5 S and 5% LDHCd 0.5 Zn 0.5 Cd 3d fine spectrum of S, pure Cd 0.5 Zn 0.5 The peaks of S at 410.8eV and 404.1eV are attributed to Cd 3d 3 / 2 and Cd 3d 5 / 2 . Figure 4 (b) is Cd 0.5 Zn 0.5 S and 5% LDH / Cd 0.5 Zn 0.5The Zn 2p fine spectrum of S, where the peaks at 1043.7 and 1020.8 eV correspond to pure Cd 0.5 Zn 0.5 Zn 2p of S 1 / 2 and Zn2p 3 / 2 . Figure 4 The XPS spectrum of S2p in (c) is divided into two independent peaks, centered at 161.8 eV and 160.6 eV, corresponding to S2p 1 / 2 and S2p 3 / 2 . With pure Cd 0.5 Zn 0.5 Compared with S, 5% LDH / Cd 0.5 Zn 0.5 The same peak of S shifts to higher energy, indicating that Cd 0.5 Zn 0.5 There is a strong electronic interaction at the interface between S and FeCo-LDH. Figure 4 (d) shows the Fe 2p spectrum of pure FeCo-LDH, where the peak at 712.7 eV is attributed to the Fe 2p 3 / 2 , the peak at 724.8 eV is attributed to Fe 2p 1 / 2 , indicating that the main iron species in FeCo-LDH is Fe 2+ , the satellite bands appearing near the main peak of Fe 2p are Fe 3+ Valence. Figure 4 The Co 2p spectrum of pure FeCo-LDH in (e) is divided into two peaks at 781.6 eV and 797.4 eV, which are respectively attributed to Co 2+ Co 2p 3 / 2 and Co 2p 1 / 2 The satellite peaks close to the two main peaks of Co indicate the presence of Co in FeCo-LDH. 3+ The O1s spectrum of pure FeCo-LDH is shown in Figure 4 As shown in (f), the peaks at 529.6 eV, 531.5 eV and 532.5 eV are related to the presence of metal O (MO), hydroxyl and carboxyl groups, respectively. 0.5 Zn 0.5 Compared with FeCo-LDH, 5% LDH / Cd 0.5 Zn 0.5 The corresponding peak positions of S shifted to different degrees, indicating that Cd 0.5 Zn 0.5 The strong electronic interaction between S and FeCo-LDH interface further confirmed that the 5% LDH / Cd 0.5 Zn 0.5 S sample was successfully prepared.
[0051] 3. Light absorption characteristics of samples and photogenerated carrier separation efficiency
[0052] The light absorption capacity of the samples was analyzed by UV-vis DRS. Figure 5 As shown in (a), FeCo-LDH exhibits excellent light absorption ability, with strong absorption from ultraviolet light to near-infrared light, among which the light absorption between 400-800nm is mainly attributed to the dd transition of Fe / Co ions. 0.5 Zn 0.5 After the composite of FeCo-LDH and Cd 0.5 Zn 0.5 The band gap width (E g )(like Figure 5 (b)), E g They are 1.64eV and 2.31eV respectively. Figure 5 (c) FeCo-LDH, Cd 0.5 Zn 0.5 S and 5% LDH / Cd 0.5 Zn 0.5 TRPL spectrum of S.
[0053] FeCo-LDH、Cd 0.5 Zn 0.5 S and 5% LDH / Cd 0.5 Zn 0.5 The carrier lifetimes of S are 1.14ns, 1.06ns and 1.45ns respectively. The composite sample 5% LDH / Cd 0.5 Zn 0.5 The carrier lifetime of S is longer than that of pure Cd 0.5 Zn 0.5 S and FeCo-LDH are long, indicating that the sample 5% LDH / Cd 0.5 Zn 0.5 The photogenerated carrier transfer efficiency of S is high. Figure 5 (d) Transient photocurrent of different samples, 5% LDH / Cd 0.5 Zn 0.5 The S composite showed the highest photocurrent, further confirming that the 5% LDH / Cd 0.5 Zn 0.5 S has the strongest separation and transfer efficiency of photogenerated carriers, which improves the photocatalytic activity. Application example LDH / Cd 1-x Zn x Evaluation of hydrogen production coupled with plastic degradation performance of S composite photocatalyst
[0054] Evaluation of photocatalytic hydrogen production performance. The photocatalytic H2O cracking to produce H2 activity test was carried out in a sealed glass circulation system (Beijing Zhongjiao Jinyuan Technology Co., Ltd.). 30 mg of catalyst was dispersed in 70 ml of 0.031 wt% polyethylene terephthalate (PET) alkaline solution. Before the reaction started, nitrogen was passed through the system for 40 minutes to remove the air in the reactor. A 300 W xenon lamp was placed vertically on the top of the reactor, supplemented by a wavelength > 420 nm visible light filter as a visible light source. The gas products were detected by GC-7900. The chromatogram consisted of a single TCD detector and The reaction temperature was maintained at 5°C by condensing circulating water.
[0055] Analysis of photocatalytic plastic degradation products. 450 μL of solution was taken from the solution before and after the photocatalytic reaction and analyzed by nuclear magnetic resonance hydrogen spectrometer ( 1 H-NMR) was used to analyze the liquid products before and after the photocatalytic reaction and to study the oxidation process of PET degradation.
[0056] LDH / Cd 0.5 Zn 0.5 The results of the photocatalytic hydrogen production and PET plastic degradation performance analysis are as follows Figure 6 shown.
[0057] Figure 6 is the hydrogen production activity of different synthetic samples in PET plastic solution. Figure 6 (a) It can be seen that Cd 0.5 Zn 0.5 S, 1% LDH / Cd 0.5 Zn 0.5 S, 3% LDH / Cd 0.5 Zn 0.5 S, 5% LDH / Cd 0.5 Zn 0.5 S and 7% LDH / Cd 0.5 Zn 0.5 The photocatalytic hydrogen production rates of S were 1.61 mmol·g -1 ·h -1 , 2.41mmol·g -1 ·h -1 , 2.74mmol·g -1 ·h -1 、3.67mmol·g -1 ·h -1 and 1.79mmol·g -1 ·h -1 . Pure Cd 0.5 Zn 0.5The unsatisfactory hydrogen production effect of S in PET plastic solution can be attributed to its fast recombination rate of photogenerated carriers. 0.5 Zn 0.5 After S is combined with LDH, the sample is 5% LDH / Cd 0.5 Zn 0.5 The photocatalytic hydrogen production rate of S reached 3.67 mmol·g -1 ·h -1 , for pure Cd 0.5 Zn 0.5 S is 2.28 times. When LDH / Cd is further increased 0.5 Zn 0.5 The amount of LDH loaded in S will reduce the photocatalytic hydrogen production activity. This is because excessive LDH will inhibit the hydrogen production activity. In other words, when an appropriate amount of LDH is loaded, more reaction sites will be provided, which will accelerate the separation and transfer of electrons and facilitate the generation of hydrogen. Once the LDH is loaded in excess, it will reduce the activity of Cd 0.5 Zn 0.5 S absorbs light, thereby reducing the activity of hydrogen evolution. 1 H-NMR was used to identify the degradation products during the photocatalytic hydrogen production coupled with PET plastic degradation. Figure 6 As shown in (b), before the reaction, PET plastic was mainly decomposed into ethylene glycol (3.58 ppm) and a small amount of acetate (1.93 ppm) in an alkaline medium. After the photocatalytic reaction, ethylene glycol was almost completely converted into acetate, and no other products were obviously detected except for a very small amount of methanol. This result confirms that the purpose of plastic degradation was achieved while hydrogen was produced.
[0058] In addition, compared with the system that also uses plastic degradation as the oxidation half-reaction (Liu Xuan, 2022, Preparation of carbon nitride-based composite photocatalysts and photocatalytic hydrogen evolution coupled microplastic degradation performance research [D]. Nanjing: Nanjing University of Science and Technology), the catalytic degradation of the system described in the present invention has two advantages: (1) Ethylene glycol is completely converted, which proves the high activity of the catalytic system from the side; (2) The degradation product is single, which is conducive to the collection and purification of the later products, increasing the practical application value. The PET packaging bottles of commercial beverages were further used as the coupled degradation material, and the results obtained were almost the same as those using PET plastics, further proving the practical application value of the system.
[0059] In summary, the present invention constructs LDH / Cd 0.5 Zn 0.5 The S catalyst photocatalyzes water decomposition to produce hydrogen, and is coupled with the degradation of PET plastics into high value-added chemicals. Through XRD, TEM, XPS, UV-vis DRS and electrochemical tests, the LDH / Cd 0.5 Zn 0.5The crystal structure, morphology and light absorption ability of S. The experimental results show that due to the 0.5 Zn 0.5 The interaction between S effectively promotes the charge separation and transfer process, thereby improving the photocatalytic efficiency. 0.5 Zn 0.5 The hydrogen evolution rate of S can reach 3.67mmol·g -1 ·h -1 In addition, the organic small molecules produced by the degradation and oxidation of plastics are 1 H-NMR spectrum analysis revealed that acetate and a small amount of methanol were produced.
[0060] The catalyst of the invention can be used to prepare a high-selectivity photocatalytic system and can be applied to the fields of plastic photoreforming and hydrogen production.
[0061] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0062] The above is a detailed introduction to the bimetallic sulfide-based photocatalyst, preparation method and application in hydrogen production coupled with plastic degradation provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a bimetallic sulfide-based photocatalyst, characterized in that The method comprises the following steps: S1, Cd 1-x Zn x Preparation of S nanosheets: Take L-cysteine and zinc nitrate, stir them thoroughly in a diethylenetriamine (DETA) aqueous solution at room temperature, pour the mixed solution into a polytetrafluoroethylene reactor, seal it, and react at a constant temperature of 150℃±10℃ in a forced air drying oven for 4 h-6 h; The synthesized product after the reaction was completed was washed by centrifugation with water and ethanol for multiple times, dried and collected at 60 ℃±5 ℃, and the obtained powder was dissolved in DETA aqueous solution, and cadmium chloride was added under continuous stirring to make it dispersed evenly. Then the mixed solution was poured into a polytetrafluoroethylene reactor for packaging, and the reaction was carried out at a constant temperature of 180 ℃±10 ℃ in a blast drying oven for 5 h-7 h. The synthesized product after the reaction was completed was collected, washed multiple times, and dried to obtain Cd 1-x Zn x S nanosheets, the ratio of raw materials is controlled so that 0.5≤x≤0.75; S2. Preparation of FeCo-LDH: Dissolve (NH4)2Fe(SO4)2·6H2O, Co(NO3)2·6H2O, Co(NH2)2 and NH4F in an appropriate amount of water and stir continuously for more than 30 minutes to mix them evenly; transfer the mixed solution to a polytetrafluoroethylene-lined autoclave and react at 120 ℃±5 ℃ for 7 h-8 h. After the reaction is completed, cool it to room temperature, wash it with deionized water and anhydrous ethanol by centrifugation at least three times to collect the sample, and finally dry it in a vacuum oven at 80 ℃±5 ℃ overnight to obtain the sample FeCo-LDH; S3, FeCo-LDH / Cd 1-x Zn x Preparation of S composite photocatalytic materials: FeCo-LDH and Cd 1-x Zn x S is mixed in a mass ratio of 1-7:100, ultrasonically dispersed in an appropriate amount of anhydrous ethanol for 2-3 h, and then evaporated to dryness in a water bath to obtain a bimetallic sulfide-based photocatalyst.
2. The preparation method according to claim 1, characterized in that: FeCo-LDH and Cd in S3 1-x Zn x The mass ratio of S is 5-7:
100. FeCo-LDH and Cd 1-x Zn x The optimal mass ratio of S is 5:
100.
3. The preparation method according to claim 1, characterized in that: S1, in the DETA aqueous solution mixed with L-cysteine and zinc nitrate, the volume ratio of DETA to H2O is 4:1; in the DETA aqueous solution in which the obtained powder is dissolved, the volume ratio of DETA to H2O is 2:
1.
4. The preparation method according to claim 1, characterized in that: In Cd 1-x Zn x In the preparation of S, when x = 0.5, the dosage ratios of L-cysteine, zinc nitrate, and cadmium chloride were 6 mmol: 6 mmol: 0.6 mmol, respectively; When x = 0.75, the dosage ratios of L-cysteine, zinc nitrate and cadmium chloride are 6 mmol:6 mmol:0.3 mmol, respectively.
5. The preparation method according to claim 1, characterized in that: In S2, the usage ratio of (NH4)2Fe(SO4)2·6H2O, Co(NO3)2·6H2O, Co(NH2)2 and NH4F is 1.2 mol:2.4 mol:4.8 mol:4.8 mol.
6. The preparation method according to claim 1, characterized in that: Cd 1-x Zn x The x in S is 0.5, FeCo-LDH and Cd 1- x Zn x The mass ratio of S is 5:
100.
7. A bimetallic sulfide-based photocatalyst prepared according to the preparation method of claim 1.
8. Use of the bimetallic sulfide-based photocatalyst according to claim 7 in hydrogen production coupled with plastic degradation.
9. The use according to claim 8, characterized in that: In a sealed environment, 30-50 mg of the catalyst was dispersed in 70 ml of a 0.025 wt%-0.035 wt% polyethylene terephthalate (PET) alkaline solution for reaction, and the reaction temperature was maintained at 5 °C.